Discovery and validation of a CD4 binding aptamer through Crossover SELEX towards the preliminary development of a point-of-care aptasensor for rapid CD4+ T-cell counting - Fellows, Tamika (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2018)
Expected release date-April 2020
Keywords: Uncatalogued